A Comprehensive View of the β-Arrestinome - Crépieux, Pascale; Poupon, Anne; Langonné-Gallay, Nathalie; Reiter, Eric; Delgado, Javier; Schaefer, Martin H.; Bourquard, Thomas; Serrano, Luis; Kiel, Christina (Frontiers in Endocrinology, 2017)
G protein-coupled receptors are membrane receptors critically involved in sensing the environment and orchestrating physiological processes. As such, they transduce extracellular signals such as hormone, neurotransmitters, ions, light, etc, into an integrated cell response. The intracellular trafficking, internalization and signaling ability of ligand-activated G protein-coupled receptors is controlled by arrestins, adaptor proteins that they interact with upon ligand binding. β-arrestins 1 and 2 in particular are now considered as hub proteins assembling multiprotein complexes to regulate receptor fate and transduce diversified cell responses. While more than four hundreds β-arrestin interaction partners have been identified so far, much remains to be learnt on how discrimination between so many binding partners is accomplished. Here, we gathered the interacting partners of β-arrestins through database mining and manual curation of the literature, to map the β-arrestin interactome (β-arrestinome). We discussed several parameters that determine compatible (AND) or mutually exclusive (XOR) binding of β-arrestin interactors, such as structural constraints, intracellular abundance or binding affinity.